2014
DOI: 10.3386/w20666
|View full text |Cite
|
Sign up to set email alerts
|

Whither News Shocks?

Abstract: Does news about future productivity cause business-cycle fluctuations? What other effects might it have? We explore the answer to this question using semi-structural VARs, where "news" is defined as the innovation in the expectation of TFP at a fixed horizon in the future. We find that systems incorporating a number of forward-looking variables, including stock prices, consumption, consumer confidence and inflation, robustly predict three outcomes. First, following a news shock, TFP rises for several years. Se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(48 citation statements)
references
References 14 publications
2
46
0
Order By: Relevance
“…More recently, however, Barsky and Sims (2011) and Barsky, Basu and Lee (2014) have used medium run restrictions and series on consumer confidence to identify news shocks and found that news shocks did not generate business cycle fluctuations. In particular, hours fell when news arrived.…”
Section: News About Future Technology Changesmentioning
confidence: 99%
“…More recently, however, Barsky and Sims (2011) and Barsky, Basu and Lee (2014) have used medium run restrictions and series on consumer confidence to identify news shocks and found that news shocks did not generate business cycle fluctuations. In particular, hours fell when news arrived.…”
Section: News About Future Technology Changesmentioning
confidence: 99%
“…The exit rate δn is set to 0.03, in line with the values used in the literature (Bilbiie, Ghironi, and Melitz () and Kung and Schmid ()). The capital depreciation rate in the steady state δk is set to 0.03, again, in line with the value used in the literature (e.g., Barsky, Basu, and Lee ()). Following Del Negro, Eggertsson, Ferrero, and Kiyotaki () and Shi (), we set the resalability of new equities θ to 0.15.…”
Section: Estimationmentioning
confidence: 99%
“…), making news shocks a potentially important source of business cycle fluctuations. Moreover, the deflationary impact of news shocks, whichBarsky, Basu, and Lee (2015) cite as one of the most robust features of the data, is no longer statistically significant.…”
mentioning
confidence: 92%
“… See Beaudry and Portier (2014) andBarsky, Basu, and Lee (2015) for excellent reviews of this literature.2 News coincide with innovations in current productivity if, for example, the successful adoption of a new technology by a firm both raises current productivity and provides news that other firms will adopt the same technology in the future.3 A separate question is whether changes in expectations about future productivity are exogenous -as the news literature typically assumes -or whether these changes are related to other shocks. While not of immediate importance for the issue of whether imposing the zero impact restriction is appropriate or not, we return to this question below when we assess the empirical implications of our alternative identification approach.…”
mentioning
confidence: 99%